Combined effect of boundary layer formation and surface smoothing on friction and wear rate of lubricated point contacts during normal running-in processes - Yazhao Zhang; Alexander Kovalev; Yonggang Meng (Friction)
Abstract The combined effect of boundary layer formation and surface smoothing on friction and wear rate of metallic surfaces under lubricated point contact condition was investigated. The double trend of friction coefficient variations was revealed during running-in and sub-running-in processes. The evolution of surface topography was measured on-site using white-light interference profilometer and analyzed using bearing area curves. Comprehensive theoretical equations that explicitly express the contributions of boundary friction, adhesive friction and wear have been derived, and results obtained by these equations were compared with experimental observations. It is concluded that the theoretical models are quantitatively adequate to describe the combined effect of surface smoothing due to mechanical wear and formation of boundary films on the changes in friction and wear rate during normal running-in processes.